Assessment of Efficacy of Ketamine Nebulization on Reduction of Incidence and Severity of Postoperative Sore Throat Due To Tracheal Intubation - Sherwani, Mujahid Masood Khan (Academia Anesthesiologica International, 2020)
Background: Aim: To assess efficacy of ketamine nebulization on reduction of incidence and severity of postoperative sore throat due to tracheal intubation. Subjects and Methods: One hundred twenty patients between 18-70 years of age of any genders were randomly assigned to two groups. Group I received ketamine 50 mg (1.0 ml) in combination with 4.0 ml saline nebulization for 15 minutes and group II received 5.0 ml saline nebulisation. Each group comprised of 60 patients. After extubating, and at 2, 4, 6, 8, 12, and 24 hours post-operatively, POST monitoring was performed. Results: Group I comprised of 32 male and 28 female and group II 30 male and 30 female. The duration of surgery was 98.5 minutes in group I and 99.2 minutes in group II. ET tube size was 7.82 in group I and 7.13 mm in group II. Intraoperative cuff pressure was 23.5 cm of H2O in group I and 23.8 cm of H2O in group II. Incidence of postoperative sore throat (POST) at 0 hours was seen in 1 in group I and 7 in group II, at 2 hours in 7 in group I and 12 in group II, at 4 hours in 11 in group I and 28 in group II, at 6 hours in 7 in group I and 16 in group II, at 12 hours in 1 in group I and 9 in group II and at 24 hours in 2 in group II. Conclusion: Preoperative ketamine nebulization found to be effective method for reducing the occurrence of post-operative sore throat (POST) in patients involving GA with endotracheal intubation.